Stay or Leave Abusive Dating Relationships: Portuguese Victims’ Reasons and Barriers - Sónia Caridade; Inês Pinheiro; Maria Alzira Pimenta Dinis (Social Sciences, 2020)
The decision to stay or leave an abusive relationship is multifactorial and frequently involves a cyclic process involving several phases. This article presents a qualitative analysis regarding the reasons and barriers to stay or leave an abusive dating relationship, as well as the challenges that it implies. A semi-structured, in-depth interview was used to collect data from thirteen dating victims, aged 17–30 years and mainly female (n = 12). The emotional and affective dependence of the partner and the belief that behaviour may change emerge as the main reasons presented by the victims to remain in an abusive relationship. Shame, fear of losing the partner, and failure to recognize the abusive relationship were reported as the main barriers to leave the abusive relationship, thus making it difficult to seek help. Understanding reasons to stay in, or barriers to leave, an abusive relationship is fundamental to promoting help-seeking behaviours in victims of dating violence (DV), particularly in the case of young people, since it has serious implications in the developmental pathway of this age group.